Fashion: its relationship with fashion design and the importance of teaching (Research, Society and Development, 2020)
Fashion is a social and cultural phenomenon that expresses the values of society in terms of uses, habits and customs, in a given time, which integrates the simple use of clothes on a daily basis in a complex political and sociological context. The act of dressing is a form of non-verbal communication and clothing takes on the important role of transmitting relevant meanings from its issuer and also of placing it in its universe of belonging. In this article, the main objective is to highlight the concept of fashion and the relationship with fashion design and teaching. The methodology is based on the state of the art, in the perspective of qualitative research and in the descriptive approach based on three main works, by the authors Barthes, Bourdieu and Lipovetsky. It could be inferred that from fashion as a system based on continuous variations and in the contemporary and globalized world, the fashion designer is constantly challenged by new trends in materials and markets and by new social and behavioral concepts.